Changes in the soil bacterial community along a pedogenic gradient. Issue 1 (December 2017) - Sánchez-Marañón, Manuel; Miralles, Isabel; Aguirre-Garrido, José; Anguita-Maeso, Manuel; Millán, Vicenta; Ortega, Raul; García-Salcedo, José; Martínez-Abarca, Francisco; Soriano, Miguel
Abstract Current research on the influence of environmental and physicochemical factors in shaping the soil bacterial structure has seldom been approached from a pedological perspective. We studied the bacterial communities of eight soils selected along a pedogenic gradient at the local scale in a Mediterranean calcareous mountain (Sierra de María, SE Spain). The results showed that the relative abundance of Acidobacteria, Canditate division WPS-1, and Armatimonadetes decreased whereas that of Actinobacteria, Bacteroidetes, and Proteobacteria increased from the less-developed soils (Leptosol) to more-developed soils (Luvisol). This bacterial distribution pattern was also positively correlated with soil-quality parameters such as organic C, water-stable aggregates, porosity, moisture, and acidity. In addition, at a lower taxonomic level, the abundance of Acidobacteria Gp4, Armatimonadetes_gp4, Solirubrobacter, Microvirga, Terrimonas, andNocardioides paralleled soil development and quality. Therefore, our work indicates that the composition of bacterial populations changes with pedogenesis, which could be considered a factor influencing the communities according to the environmental and physicochemical conditions during the soil formation.